Japan-like ribbon continent rifted from a Sumatra-like continental arc system: the Cimmerian Continent - Şengör, A. M. Celâl; Altıner, Demir; Zabcı, Cengiz; Sunal, Gürsel; Lom, Nalan; Aylan, Eşref (Zeitschrift der Deutschen Gesellschaft für Geowissenschaften, 2025)
Since its existence was proposed in 1979, the majority of the authors assumed that the Cimmerian Continent had an Atlantic-type continental margin along its northern rim, in contrast to the original model. In this paper, which is a summary of a much longer paper (Şengör et al. 2023), we show that the regional geological data from the various preserved bits of the Cimmerian Continent clearly indicate that the northern margin of it was mostly of Pacific-type and in certain short distances, possibly of California-type. Our data, culled mostly from the published literature, consist mainly of reliable isotopic ages of magmatic rocks that we interpret as arc-related. We also used palaeontological data to understand the placement of the Cimmerian Continent during the Permian, when, it seems, it began parting company with the northern margin of Gondwana-Land. The main purpose of our paper is to show the great relevance of regional geological data when trying to understand geological processes and making reconstruction of former continental positions.